Specialized medical care for chronic kidney disease patients during the war in Ukraine - Kolesnyk, M.; Stepanova, N.; Kozliuk, N. (Ukrainian Journal of Nephrology and Dialysis, 2022)
Russian invasion is an unprecedented test for the Ukrainian state, Ukrainian society, and the health care system. According to the Ministry of Health of Ukraine, more than 600 healthcare facilities suffered serious damage (more than 100 hospitals and 450 pharmacies were ruined, and more than 200 emergency medical vehicles were destroyed). Patients with chronic diseases in the occupied territories and war zones are deprived of medical care and support, which is a direct threat to their lives. Chronic kidney disease (CKD) patients are one of the most vulnerable groups. Before the war, almost 10,000 patients were treated with dialysis kidney replacement therapy (KRT) and more than 1,500 had a functioning renal graft in Ukraine. The vast majority of patients with end-stage kidney disease receiving dialysis treatment were evacuated to safer regions, and some of them continued the treatment abroad. However, the war will significantly increase the number of patients in need of kidney care. In addition to the existing number of CKD patients, there will be a large group of patients with acute kidney injury (AKI) as a result of polytrauma, bleeding, injuries, or long-term compression syndrome. Currently, we cannot predict the incidence of AKI. However, according to the previously published data (18% - 34.6% of war victims), we should expect a significant increase in the population of CKD patients shortly which will require immediate changes in both organization and staffing of nephrology care. The medical community recognizes the insurmountable difficulties in providing medical support to Ukrainian citizens during the war, in particular patients receiving KRT or kidney recipients. In our opinion, special programs should be created by relevant professional associations together with the institutes of the Ministry of Health of Ukraine and the National Academy of Medical Sciences of Ukraine at both the state and regional levels in all areas. Therefore, we consider it extremely important to establish a committee for the organization of the healthcare system for CKD patients during wartime. The committee could be created within the Ukrainian Association of Nephrologists and Kidney Transplantation Specialists, for example, as the Renal Disaster Relief Task Force established by the International Association of Nephrologists. The main tasks of the committee are to create a consensus of the Ukrainian Association of Nephrologists and Kidney Transplantation Specialists on the management of CKD patients and patients with AKI during the war and the post-war period. On behalf of the Editorial Board of the Ukrainian Journal of Nephrology and Dialysis, we would like to express our sincere gratitude to all health professionals who, at the risk of their own lives, continue to save patients. All members of the Ukrainian nephrological community are doing everything possible and impossible to ensure the most adequate treatment of kidney patients in wartime. Thank you again. We pray for our heroic warriors who fearlessly defend us and defend Ukraine’s independence! Slava Ukraini! Heroiam slava!